2005
DOI: 10.1093/acprof:oso/9780199253623.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Religious Freedom in the Liberal State

Abstract: There is a growing recognition of the challenge that religions pose for pluralist, multicultural democracies. ‘Fundamentalist’ beliefs and practices test the limits of religious freedom, and seem to contradict the very basis on which liberal states protect religious liberty. Religions, moreover, are often associated with intolerance and persecution, yet insist upon religious liberty for themselves. This book inverts these stereotypes by presenting a sustained critique of how religious liberty ought to be under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…This test has been epistemologically challenging for Rastafarians, as their movement lacks any formal membership and is additionally racial, political, and cultural in nature. Though some commentators advocate that the sincerity test should only be applicable in relation to a defendant's religion (Ahdar and Leigh 2005), Mhango (2008) has suggested that the test should protect Rastafarians irrespective of whether cultural, political or religious factors dominate their claims. Though some commentators advocate that the sincerity test should only be applicable in relation to a defendant's religion (Ahdar and Leigh 2005), Mhango (2008) has suggested that the test should protect Rastafarians irrespective of whether cultural, political or religious factors dominate their claims.…”
Section: The Religious Manifestation Of Rastafarianismmentioning
confidence: 99%
“…This test has been epistemologically challenging for Rastafarians, as their movement lacks any formal membership and is additionally racial, political, and cultural in nature. Though some commentators advocate that the sincerity test should only be applicable in relation to a defendant's religion (Ahdar and Leigh 2005), Mhango (2008) has suggested that the test should protect Rastafarians irrespective of whether cultural, political or religious factors dominate their claims. Though some commentators advocate that the sincerity test should only be applicable in relation to a defendant's religion (Ahdar and Leigh 2005), Mhango (2008) has suggested that the test should protect Rastafarians irrespective of whether cultural, political or religious factors dominate their claims.…”
Section: The Religious Manifestation Of Rastafarianismmentioning
confidence: 99%
“…They expressly state that patriarchal gender relations should be allowed to persist to enable the maximisation of liberty 65 . In some academic writings there is suggestion that human rights, particularly gender equality, might stifle liberty 66 . It is interesting however that, although liberty is presented as the favoured end point for society as a whole, liberty, in this context, is implicitly a purely male right.…”
Section: The 'Liberal' Stance Of Legal Neutrality Towards Religionmentioning
confidence: 99%
“…In brief, comprehensive liberalism is a philosophical doctrine or conception of the good life based on individual autonomy and choice, and therefore excludes doctrines that do not support these values. Political liberalism recognises the inevitable existence of differing conceptions of the good life and seeks to identify the terms under which people may live alongside one another while subscribing to different comprehensive doctrines, including those which are incompatible with the ideal of individual choice (Ahdar and Leigh 2004). Dagowitz uses this distinction to claim that faith schools that inhibit a child's freedom to choose their religion are still compatible with liberal values.…”
Section: Rights: Arguments For Muslim Schoolsmentioning
confidence: 99%